Three strategies to improve your collaborative efforts - Weaver, Liz (The Latest, 2021)
Collaboration can be challenging work. We convene colleagues together and try to work collaboratively, often providing only limited support and resources to move the collective effort forward. It is no wonder that the experience of collaboration can be frustrating.
Keywords: Libre accès; OBNL